Genetic variation: Wild, cultivated and extra terrestrial - Leggett, J. Mike (MTT, 2004)
The genetic base from which many of our present day varieties have been derived is quite narrow and frequently, pedigrees trace back to varieties such as Probsteier, Landhafer, Red Algerian, Kherson, Clintland, Bond, Grey Winter and Golden Rain. It has recently been demonstrated that allelic diversity at particular loci, rather than average genetic diversity, is sensitive to oat breeding practices (Fu et al., 2003). Base broadening of the present cultivated genepool by introducing novel germplasm is becoming increasingly important and can be achieved in a number of different ways. Wild Species. Hexaploid wild oats are the choice for introgressing genes into the cultivated oat A.sativa, as hybrids are readily formed between the two species and their chromosome pairing is usually almost complete and depending on genotype, regular. Stable recombinants can usually be recovered quite rapidly. Introgression of characters from tetraploid and diploid species (with the exception of A.maroccana, A.murphyi and A.insularis) is however a protracted and complex affair but have been accomplished. Cultivated Forms. Though cultivated forms have a lack of diversity at specific loci, there is still a wealth of variation within this genepool. The study of over 1000 landrace accessions under an EU Genetic Resources project (CT99-106) has demonstrated the diversity of genotypes which could be employed to broaden the genetic base of our modern day varieties. The Extra Terestrial . The mechanisms which release variation not manifest itself in either parent in hybrid combinations, remains largely unclear, but has been attributed to de novo mutation induced by hybridity, complementary gene action or the unmasking of recessive genes (transgressive segregation). Thus although genetic diversity for some traits may be scant, it is nevertheless evident that within the cultivated oat genepool, there is still locked up and hidden variation. Fu, et al. 2003. Crop Science 43:1989 1995.
Keywords: Ka; genetic variation; germplasm; introgression; diversity